2018
DOI: 10.1002/pd.5373
|View full text |Cite
|
Sign up to set email alerts
|

The Belgian MicroArray Prenatal (BEMAPRE) database: A systematic nationwide repository of fetal genomic aberrations

Abstract: Objective With the replacement of karyotyping by chromosomal microarray (CMA) in invasive prenatal diagnosis, new challenges have arisen. By building a national database, we standardize the classification and reporting of prenatally detected copy number variants (CNVs) across Belgian genetic centers. This database, which will link genetic and ultrasound findings with postnatal development, forms a unique resource to investigate the pathogenicity of variants of uncertain significance and to refine the phenotypi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 33 publications
2
28
0
Order By: Relevance
“…Reporting policy would vary among laboratories and in different country. A recent publication showed that Belgium had a nationwide uniform approach to prenatal chromosome microarray analysis and reporting (Muys et al, ). For instance, the 15q11.2 and the 16p12.1 microdeletions, the 16p13.11 and the distal 22q11.2 microduplications were not reported while the 15q13.3 and the proximal 16p11.2 microdeletions, the distal 16p11.2 and the 22q11.2 microduplications were reported.…”
Section: Discussionmentioning
confidence: 99%
“…Reporting policy would vary among laboratories and in different country. A recent publication showed that Belgium had a nationwide uniform approach to prenatal chromosome microarray analysis and reporting (Muys et al, ). For instance, the 15q11.2 and the 16p12.1 microdeletions, the 16p13.11 and the distal 22q11.2 microduplications were not reported while the 15q13.3 and the proximal 16p11.2 microdeletions, the distal 16p11.2 and the 22q11.2 microduplications were reported.…”
Section: Discussionmentioning
confidence: 99%
“…The proximal (A‐B) 22q11.2 duplication syndrome is the most frequently reported susceptibility CNV in our Belgian prenatal population 3 . It has a Clingen score of 3 and is a susceptibility factor for developmental delay, epilepsy and dysmorphic features and can also cause microcephaly and coronary heart disease 22 .…”
Section: Susceptibility Cnvsmentioning
confidence: 99%
“…This database facilitates data sharing and communication. In a recent study, 3 analysis of the prenatal data gathered over a 3‐year period showed pathogenic variants in 1.9% of cases; 71% of these cases were cryptic. The 22q11.2 deletion syndrome was the most frequently found genomic disorder.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations